Information actions in science and technology: institutionalities, agencies and subjects - Rabello, Rodrigo (Escola de Ciência da Informação da UFMG, 2015)
Considering the influence of new agency forms - intervention and interaction among subjects - in the context of information intermediation, we aim to approach information actions in Science and Technology (S&T) taking into consideration the institutionalities involved. For such, we assume there is an influence of a theoretical model emerging in Information Science (IS) regarding current inventive and interactive form propitiated by the Web. The text is structured in two central topics bringing: i) theoretical and epistemic constructions of the information action concept; and ii) a certain interpretation oriented by the informational action in S&T construct, taking as its object the actions performed by IBICT (Brazilian Institute for Information in Science and Technology), directed towards excellence in information. Finally, we discuss how limitations of the systemic model propitiate the construction of new study objects in the model emerging in IS from theoretical innovations and counterpoints thoughts facing the diverse forms of information action, considering, for instance, the action of subjects on what concerns the validation of information in the current scenery of institutional intermediation.

Considerando a influência das novas formas de agência - intervenção e interação de sujeitos - no contexto da intermediação da informação, objetiva-se abordar ações de informação em ciência e tecnologia (C&T) à luz de institucionalidades envolvidas. Para tanto, considera-se como pressuposto a influência de um modelo teórico que emerge na Ciência da Informação (CI) em contraponto a um modelo denominado de sistêmico, tendo em vista as atuais formas interventivas e interativas propiciadas com a Web. O texto está estruturado em dois tópicos centrais que trazem: i. construções teóricas e epistêmicas do conceito ação de informação; e ii. interpretação particular orientada pelo construto ação de informação em C&T, tomando como objeto ações realizadas pelo Instituto Brasileiro de Informação em Ciência e Tecnologia (IBICT), direcionadas a excelência da informação. Ao final, discorreu-se sobre como as limitações do modelo sistêmico têm propiciado a construção de novos objetos de estudo no modelo que emerge na CI, a partir de contrapontos e inovações teóricos pensados diante das diversificadas formas de ações de informação, considerando, como exemplo, a atuação dos sujeitos no que concerne à validação da informação no cenário contemporâneo de intermediação institucional.
Ações de informação em ciência e tecnologia: institucionalidades, agências e sujeitos
Keywords: Information actions; Information in science and technology; Information Science; Instituto Brasileiro de Informação em Ciência e Tecnologia; Ações de informação; Informação em ciência e tecnologia; Ciência da Informação; IBICT